18-Month Clinical Evaluation of Universal Adhesive Applied in No-Waiting Technique. (2022) - Almeida, RAM; Siqueira, FSF; Reis, A.; Ferreira, MWC; Bandeca, MC; Cardenas, AFM; Loguercio, AD
Abstract : Purpose/Aim: To evaluate the clinical behavior of a universal adhesive applied in the no-waiting technique in non-carious cervical lesions (NCCLs). Materials and Methods: Forty-four patients participated in this study. One hundred and seventy-six restorations were assigned to four groups according to the adhesive system in the conditioning strategies and in the waiting time: Prime&Bond Active (PB), applied in the etch-and-rinse strategy (ER) and self-etch (SE) with 20 s application and Clearfil Universal Bond Quick (CQ), applied in the ER and SE strategy), in no-waiting technique. One experienced and calibrated operator made the restorations with (Filtek Z-350 XT) composite resin using the incremental technique. The restorations were evaluated at baseline and after 18 months using both the World Dental Federation (FDI) and the United States Public Health Service (USPHS) criteria. Statistical analyses were performed with Friedman repeated measures analysis of variance by rank and McNemar test for significance in each pair. Results: Ten restorations (2 for PB-ER, 4 for PB-SE, and 4 for CQ-SE) were lost after 18 months. Had a retention rate of 95, 45% for PB-ER, 90, 9% for PB-SE, 90, 9% for CQ-SE and 100% for CQ when using the ER adhesive strategy (p > 0.05 for either criterion). Seventeen restorations showed some discrepancies in marginal adaptation at the 18-month recall using the FDI criteria (2 for PB-ER, 2 for PB-SE, 4 for CQ-ER, and 9 for CQ-SE), but only three restorations were scored as bravo for marginal adaptation in the USPHS criteria (3 for CQ-SE; p > 0.05). Conclusions: The clinical performance of the CQ adhesive in the "no waiting" technique was similar to the PB adhesive in conventional application (20 s), promoting very satisfactory results when applied in the ER or SE strategy, after 18 months of clinical evaluation in non-carious cervical lesions.